The genus Jembra Metcalf and Horton from Taiwan with descriptions of two new species and the nymph of J. taiwana sp. nov. (Hemiptera: Cercopoidea: Aphrophoridae) - Shih, Hsien-Tzung; Liang, Ai-Ping; Yang, Jeng-Tze (Zootaxa, 2009)
The genus Jembra Metcalf and Horton comprises five species from Taiwan and China. In this paper, the fauna of the genus from Taiwan is reviewed and includes three species. Two new species, J. kuanae sp. nov. and J. taiwana sp. nov., are described, and J. inouyei Matsumura is redescribed. The fourth and fifth instar nymph of J. taiwana sp. nov. is described for the first time. A dichotomous key for the identification of the five species of Jembra is also presented.